GRAN MINERÍA AURÍFERA Y SUS REPERCUSIONES EN EL DESARROLLO ECONÓMICO LOCAL* - López Más, Johans Julio (2006)
New corporate practices are being used by mining companies in Perú. Mining activity has related microeconomic impacts (income improvements, life condition changes), macroeconomic (foreing currency income, employment, etc.) social and environmental, which can constitute a conflict source if do not harmonize the corporation and its productive processes with communities settled in the inmediate environment. In the same way, it is necessary to understand that corporates are one of several performers in the territory, actors that possesses different interests and negotiation skills, for that reason is necessary be understanded that articulation of corporates in the local economic development supposes the adoption of policies to mitigate the possible negative impacts. The experience of Barrick Mining Company and its relationship with the Jangas community in Ancash is a characteristic example of this phenomenon.